New host and distribution records for Buprestidae (Coleoptera) from the state of Morelos, Mexico - Reyes-González, Roberto; Toledo-Hernández, Víctor Hugo; Torres-Manjarrez, Ana Gabriela; Flores-Palacios, Alejandro; Corona-López, Angélica María (Zootaxa, 2021)
New state and host records are provided for 28 species of Buprestidae collected in Morelos, Mexico in the following genera: Acmaeodera Eschscholtz 1829, Actenodes Dejean 1833, Agrilus Curtis 1825, Brachys Dejean 1833, Chrysobothris Eschscholtz 1829, Leiopleura Deyrolle 1864, Lius Deyrolle 1864, Pachyschelus Solier 1833, and Tetragonoschema Thomson 1857.